Quantum mechanical and quasiclassical Born-Oppenheimer dynamics of the reaction N2(X1?g+) + O(3P) ? N(4S) plus NO(X2?) on the N2O (a)over-tilde3A and (b)over-tilde3A? surfaces - Akpinar, Sinan; Armenise, Iole; Defazio, Paolo; Esposito, Fabrizio; Gamallo, Pablo; Petrongolo, Carlo; Sayos, Ramon (Elsevier Science Bv, 2012)
We present the quantum mechanical (QM) and quasiclassical trajectory (QCT) dynamics of the title reaction on two uncoupled surfaces, using a wavepacket (WP) method and considering some N-2(v,j) vibrational and rotational states. The reaction is investigated by calculating initial-state-resolved reaction probabilities, cross sections, and rate constants, which are explained in terms of energy profiles and collision mechanisms. These properties reflect the large endo-thermicity of the reaction and the features of the surfaces. Indeed, at low v values we obtain large thresholds and the lower surface is more reactive than the higher one, whereas at high v the thresholds decrease or disappear and the upper surface becomes more reactive. QM and QCT results are in satisfactory agreement, except some differences at low or high collision energy and temperature. QCT rate coefficients agree also with some published results. WP snapshots and movies of QCT time evolution show clearly abstraction and insertion mechanisms depending on the initial conditions. Insertion proceeds via a reaction complex and we observe a QM Feshbach resonance for a specific initial condition. On the overall, the dynamical observables are consistent with the collision mechanisms. (C) 2011 Elsevier B. V. All rights reserved.
Keywords: Reaction dynamics; Vibrational effects; Insertion and abstraction mechanisms; WP and QCT snapshots